2020
DOI: 10.1101/2020.02.03.932665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High contiguity long read assembly ofBrassica nigraallows localization of active centromeres and provides insights into the ancestralBrassicagenome

Abstract: High contiguity long read assembly of Brassica nigra allows localization of activecentromeres and provides insights into the ancestral Brassica genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…Likewise, hAT superfamilies of MITEs were identified and characterized in various species including B. rapa and B. oleracea, Oryza species, Musa species, and Beta vulgaris and were found to be present at high copy numbers (Bundock and Hooykaas, 2005;Muehlbauer et al, 2006;Nouroz et al, 2015b). MITEs comprised approximately 1% of the B. nigra genome (Perumal et al, 2020), and in our analysis we identified two hAT families that are largely specific to the B-genome. Genome or lineage specific amplification of transposons including MITEs has been observed for many species (Feschotte et al, 2002;Choi et al, 2014) and has been suggested to play a role not only in increasing genome size but more specifically in genome adaptation (Parisod et al, 2010;Belyayev, 2014).…”
Section: Discussionsupporting
confidence: 51%
“…Likewise, hAT superfamilies of MITEs were identified and characterized in various species including B. rapa and B. oleracea, Oryza species, Musa species, and Beta vulgaris and were found to be present at high copy numbers (Bundock and Hooykaas, 2005;Muehlbauer et al, 2006;Nouroz et al, 2015b). MITEs comprised approximately 1% of the B. nigra genome (Perumal et al, 2020), and in our analysis we identified two hAT families that are largely specific to the B-genome. Genome or lineage specific amplification of transposons including MITEs has been observed for many species (Feschotte et al, 2002;Choi et al, 2014) and has been suggested to play a role not only in increasing genome size but more specifically in genome adaptation (Parisod et al, 2010;Belyayev, 2014).…”
Section: Discussionsupporting
confidence: 51%
“…In contrast, the previous studies reported that five MATE subfamilies were identified in tomato [ 4 ] and C . sinensis [ 25 ], six were identified in potato [ 36 ], and seven were identified in maize [ 22 ], indicating a functional diversification among plant species in the complex plant processes. In addition, phylogenetic analysis revealed that all of the MATE family genes from Brassicaceae are closely associated with AtMATE genes within the same groups ( Figure 1 ) and exhibited similar exon–intron structures ( Figure 4 ), indicating that members within the subfamily have highly conserved and might have similar functions in the same groups [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no systematic and comprehensive study of this family is reported among Brassicaceae species. To date, with the completion of five Brassicaceae species ( B. napus , B. oleracea , B. rapa , B. juncea , and B. nigra ) genome sequencing [ 29 , 32 , 33 , 34 , 35 , 36 ], an investigation of the MATE gene family in Brassicaceae is now feasible and can not only provide insights into the evolutionary mechanisms of hybridization (allopolyploidy) among these species, but also lay a theoretical basis for a clearer understanding of the mechanisms involved in plant stress defense.…”
Section: Introductionmentioning
confidence: 99%
“…SMARTdenovo has been available since 2015 on github, but its performance not only remains comparable with current assemblers, and but also has several advantages as described. Furthermore, given its excellent performance for use on corrected long sequence reads, it continues to be widely used in for genome assembly projects today [33][34][35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%